Effect of postoperative systemic prednisolone on short-term and long-term outcomes in chronic rhinosinusitis with nasal polyps: A multi-centered randomized clinical trial - Müller, Sarina Katrin; Wendler, Olaf; Mayr, Susanne; Traxdorf, Maximilian; Hosemann, Werner; Olze, Heidi; Steinhart, Helmut; Wiegand, Susanne; Teymoortash, Afshin; Kuehnel, Thomas; Hackenberg, Stephan; Hummel, Thomas; et al. (Frontiers in Immunology, 2023)
Introduction: The objective of this study was to determine whether postoperative additive systemic steroid administration in chronic rhinosinusitis with nasal polyps (CRSwNP) impacted selected endoscopic, subjective and objective outcome measures. Methods: This was a prospective, randomized, double-blind, placebo-controlled, noninferiority multicenter trial of n=106 patients with CRSwNP. All patients underwent primary functional endoscopic sinus surgery (FESS) followed by topical nasal steroids. Patients were randomized to a systemic steroid or placebo for 1 month. Patients were followed up for 2 years over 9 time points. The primary outcome measures were the differences between groups with respect to the nasal polyp score (NPS) and sinonasal quality of life (SNQoL). Secondary outcome measures included interactions with respect to the Lund-Kennedy score (LKS), sinonasal symptoms, general quality of life (GQoL), 16-item odor identification test scores, recurrence rates, need for revision surgery and mucus biomarker levels. Results: 106 patients were randomized to either the placebo or the systemic steroid group (n=53 per group). Postoperative systemic steroids were not superior to placebo with respect to all primary (p= 0.077) and secondary outcome measures (p>0.05 for all). Reported adverse events were similar between the two groups. Conclusion: In conclusion, the addition of postoperative systemic steroids after primary FESS did not confer a benefit over topical steroid nasal spray alone with respect to NPS, SNQOL, LKS, GQOL, sinonasal symptoms, smell scores, recurrence rates, the need for revision surgery or biomarkers over a short-term follow-up of up to 9 months and a long-term follow-up of up to 24 months in CRSwNP patients. Functional endoscopic surgery did, however, show a strong effect on all outcome measures, which remained relatively stable up to the endpoint at 2 years.
CRIS-Team Scopus Importer:2023-03-31
Keywords: chronic rhinosinusitis; long-term; nasal polyp (NP); postoperative; prednisolone; randomized controlled trial

Excretion of urinary histamine and N-tele methylhistamine in patients with gastrointestinal food allergy compared to non-allergic controls during an unrestricted diet and a hypoallergenic diet - Raithel, Martin; Hagel, Alexander; Albrecht, Heinz; Zopf, Yurdagül; Naegel, Andreas; Baenkler, Hanns-Wolf; Buchwald, Fred; Schultis, Hans-Wolfgang; Kressel, Juergen; Hahn, Eckhart Georg; Konturek, Peter (BMC Gastroenterology, 2015)
Patients with gastrointestinal food allergy are characterised by increased production of mast cell derived mediators upon allergen contact and present often with unspecific symptoms. The aim of this study was to evaluate urinary histamine and methylhistamine excretion in patients with food allergy and to compare their values with food-tolerant controls.In a retrospective case control study the urinary excretion parameters were analysed from 56 patients (40.9, 19 - 58 years) in whom later food challenge tests confirmed food allergy. During their diagnostic work-up urine was collected during a 12-h period under an unrestricted diet with staple foods and a hypoallergenic potato-rice-diet (each 2 days). Healthy controls underwent the same diet types to define normal excretion parameters. Urinary histamine and n-methylhistamine were determined by ELISA or tandem mass spectrometry, respectively, and were expressed as median (25 - 75% range, ?g/mmol creatinine x m(2)BSA).During unrestricted diet urinary histamine was significantly higher in gastrointestinal food allergy than healthy controls (1.42, 0.9 - 2.7 vs 0.87, 0.4 - 1.3; p < 0.0001), while the difference between both groups became marginal during potato-rice diet (1.30, 0.7 - 2.1 vs 1.05, 0.5 - 1.5; p = 0.02). N-methylhistamine was found to be significantly elevated in gastrointestinal food allergy both during unrestricted diet (7.1, 5.0 - 11.2) and potato-rice diet (5.7, 3.7 - 8.7) compared to controls (p < 0.0001). Interestingly, urinary methylhistamine excretion (p < 0.004) and clinical symptom score (p < 0.02) fell significantly when the diet was switched from unrestricted to hypoallergenic food, but was not correlated with symptom scores.In gastrointestinal food allergy significantly higher levels of urine histamine and methylhistamine excretion were found under unrestricted diet, reflecting an increased secretion of histamine due to offending foods. Measurement of urinary n-methylhistamine levels may help to find out patients with increased histamine production and/or food-allergen induced clinical symptoms, respectively.
EVALuna2:2029

First Presentation of idiopathic Mast Cell Activation Syndrome (MCAS) in a Young Person: Association with Histamine and Salicylate Intolerance as well as an important Differential Diagnosis in gastroenterological Problem Patients - Raithel, Martin; Rechenauer, Tobias; Goetze, Thomas; Siebenlist, Gregor; Rueckel, Aline; Baenkler, Hanns-Wolf; Hartmann, Arndt; Haller, Florian; Hoerning, Andre (INTERNIST, 2019)
CRIS-Team WoS Importer:2019-05-17

Idiopathic Mast Cell Activation Syndrome With Associated Salicylate Intolerance - Rechenauer, Tobias; Raithel, Martin; Goetze, Thomas; Siebenlist, Gregor; Rueckel, Aline; Baenkler, Hanns-Wolf; Hartmann, Arndt; Haller, Florian; Hoerning, Andre (Frontiers in Pediatrics, 2018)
Idiopathic mast cell activation syndrome can be a rare cause for chronic abdominal pain in children. It remains a diagnosis by exclusion that can be particularly challenging due to the vast variety of possible clinical manifestations. We present a 13-year-old boy who suffered from a multitude of unspecific complaints over a long period of time. In this case, an assessment of mast cell-derived metabolites and immunohistochemical analysis of bioptic specimen was worthwhile. After ruling out, primary (oncologic) and secondary causes for mast cell activation, pharmacologic treatment adapted to the patient's salicylate intolerance resulted in a major relief of symptoms.
EVALuna2:34101

The AP-1 Transcription Factor c-Jun Promotes Arthritis by Regulating Cyclooxygenase-2 and Arginase-1 Expression in Macrophages - Hannemann, Nicole; Jordan, Jutta; Paul, Sushmita; Reid, Stephen; Baenkler, Hanns-Wolf; Sonnewald, Sophia; Bäuerle, Tobias; Vera, Julio; Schett, Georg; Bozec, Aline (Journal of Immunology, 2017)
Activation of proinflammatory macrophages is associated with the inflammatory state of rheumatoid arthritis. Their polarization and activation are controlled by transcription factors such as NF-?B and the AP-1 transcription factor member c-Fos. Surprisingly, little is known about the role of the AP-1 transcription factor c-Jun in macrophage activation. In this study, we show that mRNA and protein levels of c-Jun are increased in macrophages following pro- or anti-inflammatory stimulations. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment cluster analyses of microarray data using wild-type and c-Jun-deleted macrophages highlight the central function of c-Jun in macrophages, in particular for immune responses, IL production, and hypoxia pathways. Mice deficient for c-Jun in macrophages show an amelioration of inflammation and bone destruction in the serum-induced arthritis model. In vivo and in vitro gene profiling, together with chromatin immunoprecipitation analysis of macrophages, revealed direct activation of the proinflammatory factor cyclooxygenase-2 and indirect inhibition of the anti-inflammatory factor arginase-1 by c-Jun. Thus, c-Jun regulates the activation state of macrophages and promotes arthritis via differentially regulating cyclooxygenase-2 and arginase-1 levels.
EVALuna2:13412